2019
DOI: 10.1186/s13046-019-1232-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of RNA polymerase III transcription by Triptolide attenuates colorectal tumorigenesis

Abstract: Background Upregulation of RNA polymerase (Pol) III products, including tRNAs and 5S rRNA, in tumor cells leads to enhanced protein synthesis and tumor formation, making it a potential target for cancer treatment. In this study, we evaluated the inhibition of Pol III transcription by triptolide and the anti-cancer effect of this drug in colorectal tumorigenesis. Methods The effect of triptolide on colorectal cancer development was assessed in colorectal cancer mouse mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…The anti-inflammatory mechanism involves inhibition of NF-κB activation and DNA binding of NF-AT to enhancer sites in the IL-2 promoter [115]. Triptolide is a global transcriptional inhibitor of RNAP I, II and III [116][117][118][119], which partly explains its anti-cancer properties. Triptolide inhibits both total RNA and mRNA de novo synthesis in A549 cells.…”
Section: Triptolidementioning
confidence: 99%
See 1 more Smart Citation
“…The anti-inflammatory mechanism involves inhibition of NF-κB activation and DNA binding of NF-AT to enhancer sites in the IL-2 promoter [115]. Triptolide is a global transcriptional inhibitor of RNAP I, II and III [116][117][118][119], which partly explains its anti-cancer properties. Triptolide inhibits both total RNA and mRNA de novo synthesis in A549 cells.…”
Section: Triptolidementioning
confidence: 99%
“…Triptolide can alter RNAP II promoter occupancy [121]. A recent paper showed that triptolide reduced the formation of TFIIIB, a multi-subunit transcription factor for RNAP III at the promoters of tRNAs and 5S rRNA in colorectal cancer cells [119].…”
Section: Triptolidementioning
confidence: 99%
“…Previous work [35] suggested that triptolide is able to induce G1 cell cycle arrest by inhibiting transcriptional activation of E2F1. Triptolide was found to reduce both tumor number and tumor size in mice carrying mutations to promote growth of adenomatous polyposis coli as well as in mice treated with azoxymethane/dextran sodium sulfate to induce cancer [36]. Triptolide effectively inhibits CRC cell proliferation, colony formation, and organoid growth in vitro, and these effects are associated with down-regulation of target genes transcribed by RNA polymerase III.…”
Section: Discussionmentioning
confidence: 99%
“…Triptolide kills colorectal cancer cells in vitro and inhibits the growth of colorectal xenografts in a mouse model (Wang et al, 2009;Oliveira et al, 2015). Recently, Liang et al tested triptolide in adenomatous polyposis coli (Apc) mutated mice where it effectively inhibited colorectal cancer proliferation (Liang et al, 2019b). Interestingly, they noted that triptolide also reduced Pol III mediated transcription by inhibiting TFIIIB formation at Pol III target genes.…”
Section: Triptolidementioning
confidence: 99%